Habitat, population structure and community consume of podocnemis unifilis and p. expansa (testudines: podocnemididae ) turtles in curare-los ingleses reserve, la pedrera, amazonas, colombia (2013)
Habitat, population structure and consume of these resources by indigenous communities are determining factors for management and conservation of amazonian chelonians. The objectives of this research were: to identify the habitat types, to describe hunting patterns and to analyze population situation Podocnemis expansa and P. unifilis adult females. Therefore we researched and catalogued every habitat type used by turtles and the use of the community in the Curare – Los Ingleses reserve during hydrologic cycle period of Caquetá River, from March 2008 to January 2009. Caimán Port was the area with most incidents of two species during low-water period. On this place there were preserved 56 nests of P. unifilis. The indigenous community consumed mostly the nests on beaches close to the river. The capture effort on this sector it was 0,78 animals/day. Indigenous used cords and camuri in low waters close to nesting beaches, capturing overwhelmingly young of P. unifilis with sizes between 15 - 35 cm (N=23; X : 25,45; DS: 0,19) and adults females 36 - 55 cm (N=16; X =43,24; DS: 5,91). From nine studied beaches, eight were used by indigenous communities for catching eggs. We recommend making managements arrangements between Traditional Indigenous Authorities Criacia (Consolidation of Curare – Los Ingleses reserve) and pani (Indigenous from Cahuinari and three isles) in Bernardo – Zumaeta sector, with the government support and ngo. The start of co-managements and monitoring activities in the habitats is important in order to recommend management options of beaches and to control capture of chelonians methods.